1991
DOI: 10.1111/j.1752-7325.1991.tb02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Concerns for the Mouth among Institutionalized Elders

Abstract: There is a widespread belief that old people do not have healthy mouths, although the reason for this neglect is not clear. A random sample of 41 long-term care facilities in Vancouver was selected--653 residents were examined and about three-quarters of them were interviewed--to find associations between variables that might influence a concern for oral health and to assess the effectiveness of multivariate models for predicting this concern. A bivariate analysis of the data, using chi-square tests, assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…28,29 There is no doubt that social interactions can be disturbed by mouth-problems, especially when the problems disturb personal appearance. 30,32 Others have suggested that this occurs when people feel that the impairments (missing teeth; loose teeth or dentures etc.) 30,32 Others have suggested that this occurs when people feel that the impairments (missing teeth; loose teeth or dentures etc.)…”
Section: Discussionmentioning
confidence: 99%
“…28,29 There is no doubt that social interactions can be disturbed by mouth-problems, especially when the problems disturb personal appearance. 30,32 Others have suggested that this occurs when people feel that the impairments (missing teeth; loose teeth or dentures etc.) 30,32 Others have suggested that this occurs when people feel that the impairments (missing teeth; loose teeth or dentures etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This may be a continuation of lifelong habits among previous cohorts who sought dental care only for emergencies and when oral pain became unbearable (9). A survey of elderly in 41 long care facilities in Vancouver revealed that utilization of dental services by this population was significantly associated with younger age, having some natural teeth, and a higher socioeconomic status (10). Given that the average age ofnursing home residents in the United States is 82, and that the majority have spent down their financial resources to become eligible for Medicaid, it may be assumed that most of the current cohort of institutionalized elderly are not ready to demand professional dental services or even daily oral hygiene maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the dental status of elders has changed from a predominance of complete dentures to natural teeth, within the last two decades. Already over two-thirds of the elderly residents in Vancouver's LTC facilities have some natural teeth (7).…”
Section: Discussionmentioning
confidence: 99%
“…At present approximately 5 percent of the population over 65 years in most Western countries are disabled to the point that they must live within the confines of a long-term care (LTC) facility. Numerous reports indicate that this population makes infrequent use of dental services (1-6), and it seems reasonably clear that this is due in large part to the difficulty of attending a dentist (7).…”
mentioning
confidence: 99%